Granting the Rights of Prisoners to the Treatment of Fellow Prisoners in Class I Medan Detention Centre - Aris Syahrudin; Rahul Ardian Fikri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The granting of the rights of prisoners to the treatment of fellow prisoners in Class I Medan detention centres on the type of punishment that can be imposed on the perpetrators of criminal offences of prisoners in Class I Medan detention centres who commit criminal offences of narcotics abuse is the right of prisoners to get a reduction in punishment if during the guidance they behave well. The nature of the research used is normative legal research and the data collection method used in this research is secondary data obtained through library research, namely by conducting research on various literatures such as books, laws, which aim to find conceptions, or notions related to the problem of Granting Rights to Prisoners Against Treatment of Fellow Prisoners in Medan Class I Detention Centre. The granting of the rights of prisoners to the treatment of fellow prisoners at the Medan Class I Detention Centre can be interpreted as a place where humans who violate the rules and norms that exist in society are gathered. While the principle adopted by correctional institutions is to position prisoners as subjects who are seen as individuals, ordinary citizens, and as creatures of God. Based on this, in the detention centre inmates receive guidance and coaching with the hope that after completing their sentence, inmates can socialise with the community and improve their skills to be able to live independently in the community.